Copper-cobalt based heterogeneous catalyst, preparation method and application thereof, and method for electrocatalytic oxidation of 5-hydroxymethylfurfural

By forming a copper-cobalt-based heterostructured catalyst on a metal foam substrate, the problem of low current density of the existing catalyst at low voltage is solved, and high current density and high selectivity are achieved Oxidation reaction.

CN118925729BActive Publication Date: 2025-02-25ZHEJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411413214.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-02-25
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The current density of the existing heterostructure catalysts in HMF electrocatalytic oxidation reaction is low at low voltage, resulting in low reaction activity and selectivity.

Method used

A copper-cobalt-based heterostructure catalyst is used, which forms a CuxO/CoOy film on the metal foam substrate by in-situ solution combustion method, enhancing the adsorption effect of HMF and OH- and reducing charge transport resistance.

Benefits of technology

The current density of the electrocatalytic oxidation reaction of HMF is significantly improved at low voltage, and the conversion rate of 5-hydroxymethylfurfural oxidation and the selectivity of 2,5-furandicarboxylic acid are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118925729B_ABST
    Figure CN118925729B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of electrocatalytic oxidation of 5-hydroxymethylfurfural, and specifically relates to a copper-cobalt-based heterogeneous structure catalyst, a preparation method and application thereof, and a method for electrocatalytic oxidation of 5-hydroxymethylfurfural. The present invention adopts an in-situ solution combustion method, uses ethylene glycol as a solvent and a fuel, and uses a soluble metal salt as an oxidant, and in-situ combustion occurs on a preheated metal foam substrate, and Cu is grown on the surface of the metal foam substrate. x O / CoO y layer, forming a copper-cobalt based heterostructure catalyst, Cu x O / CoO y The heterogeneous structure is beneficial to enhance the HMF and OH ‑ adsorption and promote charge transfer by reducing the charge transfer resistance, CoO y and Cu x O synergistically, when used to catalyze the oxidation of 5-hydroxymethylfurfural, the current density in the HMF electrooxidation reaction, the conversion rate of 5-hydroxymethylfurfural oxidation and the selectivity of 2,5-furandicarboxylic acid were simultaneously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of 5-hydroxymethylfurfural electrocatalytic oxidation, and specifically relates to a copper-cobalt-based heterostructure catalyst, a preparation method and application thereof, and a method for electrocatalytic oxidation of 5-hydroxymethylfurfural. Background Art

[0002] Biomass contains organic carbon, is renewable and has abundant reserves. Efficient biomass conversion is expected to replace traditional fossil energy synthesis routes. Among them, 5-hydroxymethylfurfural (HMF) is one of the most promising bio-based platform compounds. HMF redox products are widely used in chemical reagents, plastics, textiles and liquid fuels. More importantly, its oxidation final product 2,5-furandicarboxylic acid (FDCA) can replace a series of petroleum derivatives and has extremely high application value.

[0003] Electrocatalytic oxidation of HMF (HMFOR) to obtain FDCA is currently one of the most effective ways to catalyze the oxidation of HMF. However, in its actual application, HMF and OH − The adsorption of HMF and OH is weak, resulting in low reaction activity and selectivity of electrocatalytic oxidation of HMF to FDCA. − The adsorption effect of HMF can improve the selectivity of FDCA from electrocatalytic oxidation of HMF. Most of the existing heterogeneous catalysts are formed by depositing the active components in powder form on a substrate. However, since the active component powder and the substrate are connected by deposition, the resistance to charge transfer between the active component powder and the substrate is large, and the current density of the catalyst in HMFOR is low at low voltage (voltage ≤1.4V vs RHE). Summary of the invention

[0004] The purpose of the present invention is to provide a copper-cobalt-based heterostructure catalyst and a preparation method and application thereof, and a method for electrocatalytic oxidation of 5-hydroxymethylfurfural. The copper-cobalt-based heterostructure catalyst provided by the present invention has a high current density in HMFOR at a low voltage.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a copper-cobalt-based heterostructure catalyst, comprising the following steps:

[0007] The ethylene glycol solution of the soluble metal salt is drop-coated on the preheated metal foam substrate, and combustion occurs to form Cu on the metal foam substrate. x O / CoO y The film is obtained to obtain a copper-cobalt based heterogeneous structure catalyst; wherein 1<x<2, 1<y<4 / 3; the preheating temperature is ≥100°C;

[0008] The soluble metal salt includes a soluble cobalt salt or a soluble copper salt;

[0009] The metal foam substrate comprises a copper metal foam substrate or a cobalt metal foam substrate;

[0010] The metal element in the soluble metal salt is different from the metal element in the metal foam substrate.

[0011] Preferably, the concentration of the soluble metal salt in the ethylene glycol solution of the soluble metal salt is 0.1-1 mol / L.

[0012] Preferably, the drop coating amount of the ethylene glycol solution of the soluble metal salt is 100-400 μL / cm 2 .

[0013] Preferably, the preheating temperature is 100-180°C.

[0014] Preferably, the soluble cobalt salt comprises cobalt nitrate; and the soluble copper salt comprises copper nitrate.

[0015] The present invention provides a copper-cobalt-based heterogeneous structure catalyst prepared by the preparation method described in the above technical solution, comprising a metal foam substrate and a Cu-cobalt ... x O / CoO y film.

[0016] The present invention provides the use of the copper-cobalt-based heterostructure catalyst described in the above technical solution in the electrocatalytic oxidation reaction of 5-hydroxymethylfurfural.

[0017] The present invention provides a method for electrocatalytic oxidation of 5-hydroxymethylfurfural, comprising the following steps:

[0018] Electrolyze 5-hydroxymethylfurfural to produce an electrocatalytic oxidation reaction to obtain 2,5-furandicarboxylic acid;

[0019] The working electrode used in the electrolysis is the copper-cobalt based heterostructure catalyst described in the above technical solution.

[0020] Preferably, the electrolysis temperature is 20-80° C., and the time is 0.25-5.0 h; and the electrolyte used in the electrolysis includes potassium hydroxide aqueous solution or sodium hydroxide aqueous solution.

[0021] Preferably, the electrode system used in the electrolysis comprises a three-electrode system, and the three-electrode system comprises a working electrode, a reference electrode and a counter electrode;

[0022] The reference electrode comprises a Hg / HgO electrode;

[0023] The counter electrode includes a metal electrode or a graphite electrode.

[0024] The present invention provides a method for preparing a copper-cobalt-based heterogeneous structure catalyst, comprising the following steps: dripping an ethylene glycol solution of a soluble metal salt onto a preheated metal foam substrate, causing combustion, and forming a Cu-cobalt-based heterogeneous structure catalyst on the metal foam substrate. x O / CoO y The present invention adopts an in-situ solution combustion method, using ethylene glycol as a solvent and a fuel, and using a soluble metal salt as an oxidant, to generate in-situ combustion on a metal foam substrate (CF), and growing Cu on the surface of the metal foam substrate. x O / CoO y layer, in which Cu x CuO and Cu2O exist in O at the same time, CoO y Co3O4 and CoO coexist in the catalyst to form a copper-cobalt-based heterostructure catalyst. x O / CoO y The heterogeneous structure is beneficial to enhance the HMF and OH - adsorption and promote charge transfer by reducing the charge transfer resistance, CoO y and Cu x O synergistically, when used to catalyze the oxidation of 5-hydroxymethylfurfural, the current density in HMFOR, the conversion rate of 5-hydroxymethylfurfural oxidation and the selectivity of 2,5-furandicarboxylic acid were simultaneously improved. As shown in the examples, at voltages of 1.2 V, 1.3 V and 1.4 V (vs. RHE), the current densities of the copper-cobalt based heterostructure catalyst in HMFOR were 46.6 mA / cm 2 、172.8mA / cm 2 and 361.9mA / cm 2 Moreover, the preparation method provided by the present invention can synthesize the copper-cobalt-based heterogeneous structure catalyst in one step, which is simple to operate, low in cost, and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram of the synthesis mechanism of copper-cobalt-based heterostructure catalysts;

[0026] Figure 2 Cu x O / CoO y XRD and SEM images of @CF heterostructure catalyst, where (a) is the XRD image and (b) is the SEM image;

[0027] Figure 3 Cu x O / CoO y SEM-EDS element mapping of @CF heterostructure catalyst, where (a) is the SEM image, (b) is the Cu element mapping image, (c) is the Co element mapping image, and (d) is the O element mapping image;

[0028] Figure 4 Cu x O / CoO y High-resolution transmission electron microscopy (HRTEM) and selected area electron diffraction (SAED) images of @CF heterostructure catalysts, where (a) is the HRTEM image and (b) is the SAED image;

[0029] Figure 5 Cu x O / CoO y @CF heterostructure catalyst, Cu x O@CF catalyst and CoO y Synchrotron radiation X-ray absorption spectrum (XAFS) of @CF1 catalyst, where (a) is the X-ray absorption near-edge structure spectrum (XANES) of Cu K absorption edge, (b) is the extended X-ray absorption fine structure spectrum (EXAFS) of Cu R space, (c) is the XANES spectrum of Co K absorption edge, and (d) is the EXAFS spectrum of Co R space;

[0030] Figure 6 Cu x O / CoO y LSV curves and Cu@CF heterostructure catalysts for water oxidation reaction (OER) and 5-hydroxymethylfurfural oxidation reaction (HMFOR) x O / CoO y HMF conversion, FDCA selectivity and Faradaic efficiency of @CF heterogeneous catalysts, where (a) is Cu x O / CoO y LSV curves of @CF heterogeneous catalysts for OER and HMFOR, (b) Cu x O / CoO y @CF HMF conversion, FDCA selectivity and Faradaic efficiency of heterogeneous catalysts;

[0031] Figure 7 CoO y @CF1 catalyst, Cu x O@CF catalyst and Cu x O / CoO y @CF Current density and Tafel slope plot of heterostructure catalysts;

[0032] Figure 8 The current density bar graphs of the catalysts prepared in Example 1 and References 1 to 19 in HMFOR at low voltages (1.2 V, 1.3 V, and 1.4 V);

[0033] Fig. 9 CoO y @CF1 catalyst, Cu x O@CF catalyst and Cu x O / CoO y Electrochemical impedance spectroscopy (EIS) data of @CF heterostructure catalysts and CoO y @CF1 catalyst, Cu x O@CF catalyst and Cu x O / CoO y Open circuit potential curves (OCP) of @CF heterostructure catalyst in 1M KOH and 50mM HMF+1M KOH, where (a) is CoO x @CF1 catalyst, Cu x O@CF catalyst and Cu x O / CoO x EIS data of @CF heterogeneous catalysts, (b) CoO x @CF1 catalyst, Cu x O@CF catalyst and Cu x O / CoO x @CF OCP curves of heterogeneous catalyst in 1M KOH and 50mM HMF+1M KOH. DETAILED DESCRIPTION

[0034] The present invention provides a method for preparing a copper-cobalt-based heterostructure catalyst, comprising the following steps:

[0035] The ethylene glycol solution of the soluble metal salt is drop-coated on the preheated metal foam substrate, and combustion occurs to form Cu on the metal foam substrate. x O / CoO y The film is obtained to obtain a copper-cobalt based heterostructure catalyst; wherein 1<x<2, 1<y<4 / 3 (four thirds); the preheating temperature is ≥100°C;

[0036] The soluble metal salt includes a soluble cobalt salt or a soluble copper salt;

[0037] The metal foam substrate comprises a copper metal foam substrate or a cobalt metal foam substrate;

[0038] The metal element in the soluble metal salt is different from the metal element in the metal foam substrate.

[0039] In the present invention, unless otherwise specified, the reagents used are commercially available products well known to those skilled in the art.

[0040] Figure 1 Schematic diagram of the synthesis mechanism of copper-cobalt-based heterostructure catalysts. Figure 1 The preparation method of the copper-cobalt based heterostructure catalyst is described in detail.

[0041] In the present invention, the soluble cobalt salt preferably includes cobalt nitrate, more preferably cobalt nitrate hexahydrate; the soluble copper salt preferably includes copper nitrate, more preferably copper nitrate pentahydrate; the concentration of the soluble metal salt in the ethylene glycol solution of the soluble metal salt is preferably 0.1~1 mol / L, more preferably 0.2~0.8 mol / L, and most preferably 0.4~0.5 mol / L.

[0042] In the present invention, the drop coating amount of the ethylene glycol solution of the soluble metal salt is preferably 100-400 μL / cm 2 , preferably 150~350µL / cm 2 , the most preferred range is 200~300µL / cm 2 In the present invention, the area of ​​the metal foam substrate is preferably 0.5×2~5×5cm 2 , more preferably 1×2~3×5cm 2 , the most preferred size is 1×2~1×5cm 2 .

[0043] In the present invention, the metal foam substrate is also preheated before drop coating; the preheating temperature is preferably 100-180° C., more preferably 120-160° C., and most preferably 130-150° C. The present invention uses an in-situ solution combustion method, ethylene glycol as a solvent and fuel, and a soluble metal salt as an oxidant to produce in-situ combustion (galvanic displacement reaction) on a metal foam substrate to obtain a copper-cobalt-based heterostructure catalyst.

[0044] The present invention provides a copper-cobalt-based heterogeneous structure catalyst prepared by the preparation method described in the above technical solution, comprising a metal foam substrate and a Cu-cobalt ... x O / CoO y film.

[0045] The present invention provides the use of the copper-cobalt-based heterogeneous structure catalyst described in the above technical solution in the electrocatalytic oxidation reaction of 5-hydroxymethylfurfural. The copper-cobalt-based heterogeneous structure catalyst provided by the present invention has Cu x O / CoO y Heterostructure, CoO y and Cu xO synergistically improved the current density, conversion of 5-HMFOR oxidation, and selectivity of 2,5-furandicarboxylic acid in HMFOR.

[0046] The present invention provides a method for electrocatalytic oxidation of 5-hydroxymethylfurfural, comprising the following steps:

[0047] Electrolyze 5-hydroxymethylfurfural to produce an electrocatalytic oxidation reaction to obtain 2,5-furandicarboxylic acid;

[0048] The working electrode used in the electrolysis is the copper-cobalt based heterostructure catalyst described in the above technical solution.

[0049] In the present invention, the electrode system used in the electrolysis preferably includes a three-electrode system, and the three-electrode system includes a working electrode, a reference electrode and a counter electrode; the reference electrode preferably includes a Hg / HgO electrode, the counter electrode preferably includes a metal electrode or a graphite electrode, and the metal electrode preferably includes a platinum electrode. In the present invention, the electrolyte used in the electrolysis preferably includes a potassium hydroxide aqueous solution or a sodium hydroxide aqueous solution; the concentrations of the potassium hydroxide aqueous solution and the sodium hydroxide aqueous solution are independently preferably 0.5~1 mol / L, more preferably 0.6~1 mol / L, and most preferably 0.8~1 mol / L.

[0050] In the present invention, the electrolysis temperature is preferably 20-80°C, more preferably 25-30°C, and most preferably 25-28°C; the electrolysis time is preferably 0.25-5.0h, more preferably 0.3-0.45h, and most preferably 0.35-0.4h.

[0051] In order to further illustrate the present invention, a copper-cobalt-based heterostructure catalyst provided by the present invention, a preparation method and application thereof, and a method for electrocatalytic oxidation of 5-hydroxymethylfurfural are described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.

[0052] Example 1

[0053] The size is 1×2cm 2 The copper metal foam substrate (denoted as CF) is placed on a hot plate and heated to 140° C. to obtain a preheated copper metal foam substrate;

[0054] The ethylene glycol solution of Co(NO3)2·6H2O with a concentration of 1 mol / L was drop-coated on the preheated copper metal foam substrate, and combustion occurred, and Cu was grown on the surface of the copper metal foam substrate. x O / CoO y layer, and a copper-cobalt-based heterostructure catalyst (denoted as Cu x O / CoO y@CF heterogeneous catalyst), where the ratio of the volume of Co(NO3)2·6H2O ethylene glycol solution to the surface area of ​​the copper metal foam substrate is 200µL:1cm 2 .

[0055] The Cu prepared in Example 1 x O / CoO y @CF heterogeneous catalyst was characterized, and the results were as follows Figure 2~Figure 4 shown. Figure 2 Cu x O / CoO y XRD and SEM images of @CF heterogeneous catalyst, where (a) is the XRD image and (b) is the SEM image. Figure 2 It can be seen that the catalyst is mainly composed of Co3O4 and CuO, with Cu x O / CoO y @CF heterostructure exists in the form of Figure 2 As shown in (a), the Cu-Co-based heterostructure catalysts match the cubic size of CuO (PDF#78-0428) and Co3O4 (PDF#42-1467), respectively. Figure 2 From (b), we can see that Cu x O / CoO y Grown on the surface of a copper metal foam substrate.

[0056] Figure 3 Cu x O / CoO y SEM-EDS element mapping of @CF heterogeneous catalyst, where (a) is the SEM image, (b) is the Cu element mapping, (c) is the Co element mapping, and (d) is the O element mapping. Figure 3 It can be seen that Cu x O / CoO y layer is grown on the surface of the copper metal foam substrate, and the Cu x O / CoO y @CF heterogeneous catalysts contain Co, Cu and O elements.

[0057] Figure 4 Cu x O / CoO y High-resolution transmission electron microscopy (HRTEM) and selected area electron diffraction (SAED) images of @CF heterogeneous catalysts, where (a) is the HRTEM image and (b) is the SAED image. Figure 4 As shown in (a), in Cu x O / CoO yThere are two lattice planes on the @CF heterogeneous catalyst, with lattice spacings of 0.24, 0.21, and 0.23 nm, corresponding to CuO (111), CuO (200), and Co3O4 (222), respectively. The existence of the interface between the CuO crystal plane and the Co3O4 crystal plane indicates the formation of a CuO and Co3O4 heterogeneous structure. Figure 4 The coexistence of CuO and Co3O4 crystals is further confirmed in (b), where different diffraction rings are observed for the CuO (220), (200) (PDF#78-0428) and Co3O4 (311), (200) (PDF#42-1467) crystal planes in the heterostructure (the d spacings of Cu2O and CoO overlap with those of CuO and Co3O4, so they cannot be confirmed by TEM and XRD, but subsequent Figure 5 The presence of Cu2O and CoO can be proved).

[0058] Example 2

[0059] The size is 1×2cm 2 The cobalt metal foam substrate (denoted as CF1) is placed on a hot plate and heated to 140°C to obtain a preheated cobalt metal foam substrate;

[0060] A 1 mol / L ethylene glycol solution of Cu(NO3)2·5H2O was drop-coated on the preheated cobalt metal foam substrate, and combustion occurred, and Cu was grown on the surface of the cobalt metal foam substrate. x O / CoO y layer, and a copper-cobalt-based heterostructure catalyst (denoted as Cu x O / CoO y @CF1 heterogeneous catalyst), where the ratio of the volume of the ethylene glycol solution of Cu(NO3)2·5H2O to the surface area of ​​the cobalt metal foam substrate is 200µL:1cm 2 .

[0061] Comparative Example 1

[0062] The size is 1×2cm 2 The cobalt metal foam substrate (CF1) is placed on a hot plate and heated to 140° C. to obtain a preheated cobalt metal foam substrate;

[0063] The ethylene glycol solution of Co(NO3)2∙6H2O with a concentration of 1 mol / L was drop-coated on the preheated cobalt metal foam substrate, and combustion occurred, and CoO was grown on the surface of the cobalt metal foam substrate. y layer, and CoO y @CF1 catalyst. The ratio of the volume of Co(NO3)2∙6H2O ethylene glycol solution to the surface area of ​​the cobalt metal foam substrate is 200µL:1cm 2 .

[0064] Comparative Example 2

[0065] The size is 1×2cm 2 The copper metal foam substrate (CF) is placed on a hot plate and heated to 140° C. to obtain a preheated copper metal foam substrate;

[0066] The ethylene glycol solution of Cu(NO3)2∙5H2O with a concentration of 1 mol / L was drop-coated on the preheated copper metal foam substrate, and combustion occurred, and Cu was grown on the surface of the copper metal foam substrate. x O layer, Cu x O@CF catalyst, where the ratio of the volume of the ethylene glycol solution of Cu(NO3)2∙5H2O to the surface area of ​​the copper metal foam substrate is 200µL:1cm 2 .

[0067] Synchrotron radiation-based X-ray absorption spectroscopy (XAS) revealed that Cu x O / CoO y @CF heterostructure catalyst consists of Cu x O (Cu2O, CuO) and CoO y (Co3O4, CoO) mixed phase composition. Figure 5 Cu x O / CoO y @CF heterostructure catalyst, Cu x O@CF catalyst and CoO y Synchrotron radiation X-ray absorption spectra (XAFS) of @CF1 catalyst, where (a) is the X-ray absorption near edge structure spectrum (XANES) of Cu K absorption edge (K-edge), (b) is the extended X-ray absorption fine structure spectrum (EXAFS) of Cu R space (R space), (c) is the XANES spectrum of Co K absorption edge, and (d) is the EXAFS spectrum of Co R space. Figure 5 As shown in (a), Cu x O / CF and Cu x O / CoO y The Cu K absorption edge XANES of the @CF catalyst is different from the spectral features of Cu foil, CuO and Cu2O, indicating that both CuO and Cu2O phases exist in these two samples. In addition, in these two samples, Cu is in an oxidized state. For these two samples, the Cu R-space EXAFS spectra ( Figure 5 The strong peak at about 1.5 Å in (b) can be attributed to the Cu-O bond. Figure 5 As shown in (c), CoO y / CF1 and Cu x O / CoO yThe Co K absorption edge XANES spectral characteristics of @CF catalyst are between CoO and Co3O4, indicating the existence of two phases at the same time. Figure 5 In (d), with CoO y Compared with CF1, Cu x O / CoO y The coordination number (Co-O) and bond length (Co-O) of the @CF sample increase, revealing the strong interaction between Cu and Co atoms.

[0068] Example 3

[0069] The Cu prepared in Example 1 x O / CoO y @CF heterogeneous catalyst was used as working electrode, graphite rod as counter electrode, Hg / HgO electrode as reference electrode, 1M KOH aqueous solution as electrolyte, three-electrode system electrolysis was carried out at 25°C, and potential test was carried out using CHI 660e electrochemical workstation.

[0070] To test Cu x O / CoO y The HMF to FDCA conversion performance of the @CF heterogeneous catalyst was tested at 1.2~1.6V vs. RHE using a 10mL H-type electrolytic cell containing 10mM HMF solution and LSV detection of HMFOR at a scan rate of 5mV·sec -1 All potentials were recorded using the Hg / HgO electrode as the reference electrode, and the RHE was calculated according to the standard Nernst equation, as shown in Equation I:

[0071] E(RHE)=E(Hg / HgO)+0.098+0.059V×pH Formula I;

[0072] Where E(Hg / HgO) is the applied potential, 0.098 is the standard potential of a Hg / HgO electrode at 25°C, and pH is the pH of the electrolyte, which is 13.8.

[0073] Equipped with UV-visible detector and C 18 The concentrations of HMF, FDCA and their corresponding intermediates were monitored by a high performance liquid chromatograph (Agilent 1260 Infinity II system) with a column (2.7 μm, 4.6×100 mm). The test conditions were as follows: the wavelength of the UV detector was 265 nm; a mixed solution of 5 mM ammonium formate aqueous solution and methanol = 90:10 (v / v) was used as the mobile phase, and the elution method was isothermal elution; the separation time of the isothermal elution was 10 minutes; the mobile phase flow rate was 0.4 mL·min -1 ; injection volume was 2 µL).

[0074] Take 50 μL of the anode electrolyte solution of the above three-electrode system, dilute it with 2 mL of ultrapure water (DI H2O), and then add 50 μL of 0.5 M HCl solution to lower the pH. Calculate the conversion rate of HMF, the selectivity of FDCA and the Faraday efficiency. The calculation formulas are shown in Formulas II to IV:

[0075] HMF conversion rate (%) = n(HMF 消耗 ) / n(HMF 初始 )×100% Formula II;

[0076] Selectivity of FDCA (%) = n (FDCA) / n (product) × 100% Formula III;

[0077] Faraday efficiency (%) = n(FDCA 形成 ) / (charge / (6×F))×100% Formula IV.

[0078] Where "F" is the Faraday constant, "n" represents "the number of moles of reactants or products"; n (products) represents all products generated by the conversion of HMF. Theoretically, the total charge number of converting 10mL of 10mM HMF into FDCA is about 57.8C, assuming that the conversion of 1 molecule of HMF into FDCA requires the transfer of 6 electrons.

[0079] Figure 6 Cu x O / CoO y LSV curves and Cu@CF heterogeneous catalysts for water oxidation reaction (OER) and 5-hydroxymethylfurfural oxidation reaction (HMFOR) x O / CoO y HMF conversion, FDCA selectivity and Faradaic efficiency of @CF heterogeneous catalysts, where (a) is Cu x O / CoO y LSV curves of @CF heterogeneous catalysts for OER and HMFOR, (b) Cu x O / CoO y HMF conversion, FDCA selectivity and Faradaic efficiency of @CF heterogeneous catalysts. Figure 6 As shown in (a), compared with OER, the potential for HMFOR is 100 mA cm -2 It can be reduced to 260mV at a current density of 1.37kV, indicating that the catalyst has advantages in reducing the energy consumption of HMFOR and improving the selectivity of HMF to FDCA conversion. Figure 6 In (b), we can see that Cu x O / CoO yThe @CF heterogeneous catalyst exhibits excellent HMF conversion, Faradaic efficiency, and selectivity for FDCA.

[0080] Figure 7 CoO y @CF1 catalyst, Cu x O@CF catalyst and Cu x O / CoO y @CF Current density and Tafel slope plot of heterogeneous catalysts. Figure 7 It can be seen that the Cu provided by the present invention x O / CoO y The current density of HMFOR catalyzed by @CF heterogeneous catalyst is higher than that of single-component CoO y @CF1 catalyst and Cu x O@CF catalyst.

[0081] Comparative Example 3

[0082] The catalysts prepared in documents 1 to 19, wherein:

[0083] Document 1 (Zeng, L.; Chen, Y.; Sun, M.; Huang, Q.; Sun, K.; Ma, J.; Li,J.; Tan, H.; Li, M.; Pan, Y.; Liu, Y.; Luo, M.; Huang, B.; Guo, S., Cooperative Rh-O5 / Ni(Fe) Site for Efficient Biomass Upgrading Coupled withH2Production. Journal of the American Chemical Society 2023) Rh−O5 / Ni(Fe) catalyst prepared;

[0084] Literature 2 (Xiao, D.; Bao, -Over Controllable Reconstructed Ni (3) S (2) / NiO (x) . Advanced materials 2023, 2304133) prepared Ni3S2 / NiO x catalyst;

[0085] CuOCoOOH catalyst prepared in reference 3 (Liu, S.; Dou, S.; Meng, J.; Liu, Y.; Liu, Y.; Yu, H., Efficientbiobased carboxylic acids synthesis by synergistic electrocatalysis of multi-active sites on bimetallic Cu-Co oxide / oxyhydroxide. Applied Catalysis B: Environmental 2023);

[0086] Co prepared in Document 4 (Sun, Y.; Wang, J.; Qi, Y.; Li, W.; Wang, C., EfficientElectrooxidation of 5-Hydroxymethylfurfural Using Co-Doped Ni3S2Catalyst: Promising for H2Production under Industrial-Level Current Density. Adv Sci(Weinh) 2022, 9 (17), 2200957) 0.4 NiS@NF catalyst;

[0087] NF@Co3O4 / CeO2 catalyst prepared in reference 5 (Zhao, G.; Hai, G.; Zhou, P.; Liu, Z.; Zhang, Y.; Peng, B.; Xia,W.; Huang, X.; Wang, G., Electrochemical Oxidation of 5-Hydroxymethylfurfuralon CeO2-Modified Co3O4with Regulated Intermediate Adsorption and PromotedCharge Transfer. Advanced Functional Materials 2023, 33 (14));

[0088] CoNiFe-MOFs catalyst prepared in reference 6 (Bai, X.-J.; He, W.-X.; Lu, X.-Y.; Fu, Y.; Qi, W., Electrochemical oxidation of 5-hydroxymethylfurfural on ternary metal–organicframework nanoarrays: enhancement from electronic structure modulation. Journal of Materials Chemistry A 2021, 9 (25), 14270-14275);

[0089] CuCo2O4 catalyst prepared in reference 7 (Lu, Y.; Dong, CL; Huang, YC; Zou, Y.; Liu, Z.; Liu, Y.; Li, Y.; He, N.; Shi, J.; Wang, S., Identifying the Geometric Site Dependenceof Spinel Oxides for the Electrooxidation of 5-Hydroxymethylfurfural. Angewandte Chemie International Edition 2020, 59 (43), 19215-19221);

[0090] NiFe-1 catalyst prepared in reference 8 (Wang, C.; Wu, Y.; Bodach, A.; Krebs, ML; Schuhmann, W.; Schuth, F., A Novel Electrode for Value-Generating Anode Reactions in Water Electrolyzers at Industrial Current Densities. Angewandte Chemie 2023, 62(7), 202215804);

[0091] Reference 9 (He, Y.; Zhu, B.; Wang, F.; Xiong, J.; Akram, MA; Feng, L., Tuning the adsorption behaviors of non-noble electrocatalysts to boostvalorization of 5-hydroxymethylfurfural. Journal of Materials Chemistry A2023, 11 (26), 14284-14293) prepared O x -NiCuO z catalyst;

[0092] PtNi NWs catalyst prepared in reference 10 (Wu, J.; Kong, Z.; Li, Y.; Lu, Y.; Zhou, P.; Wang, H.; Xu, L.; Wang, S.; Zou, Y., Unveiling the Adsorption Behavior and Redox Properties of PtNi Nanowire for Biomass-Derived Molecules Electrooxidation. ACS Nano 2022,16 (12), 21518-21526);

[0093] Ni-VN / NF catalyst prepared in reference 11 (Jia, W.; Liu, B.; Gong, R.; Bian, X.; Du, S.; Ma, S.; Song, Z.; Ren, Z.; Chen, Z., Electronic Modulation Induced by Ni-VN Heterojunction Reinforces Electrolytic Hydrogen Evolution Coupled with Biomass Upgrade. Small 2023, 2302025);

[0094] Mn prepared in Reference 12 (Li, S.; Wang, S.; Wang, Y.; He, J.; Li, K.; Xu, Y.; Wang, M.; Zhao, S.; Li, X.; Zhong, X.; Wang, J., Doped Mn Enhanced NiS ElectrooxidationPerformance of HMF into FDCA at Industrial‐Level Current Density. AdvancedFunctional Materials 2023) 0.2 NiS / GF catalyst;

[0095] Literature 13 (Sun, M.; Yang, J.; Huang, J.; Wang, Y.; Liu, X.; Qi, Y.; Zhang, L., Interfacial Engineering of Ni / Ni 0.2 Mo 0.8 Ni / Ni prepared 0.2 Mo 0.8 catalyst;

[0096] Literature 14 (Ye, F.; Zhang, S.; Cheng, Q.; Long, Y.; Liu, D.; Paul, R.; Fang, Y.; Su, Y.; Qu, L.; Dai, L.; Hu, C., The role of oxygen-vacancy inbifunctional indium oxyhydroxide catalysts for electrochemical coupling of biomass valorization with CO2conversion. Nature communications 2023, 14 (1), 2040) prepared InOOH-O V catalyst;

[0097] NiVW prepared in reference 15 (Zhang, B.; Yang, Z.; Yan, C.; Xue, Z.; Mu, T., OperandoForming of Lattice Vacancy Defect in Ultrathin Crumpled NiVW-Layered MetalHydroxides Nanosheets for Valorization of Biomass. Small 2023, 2207236) v -LMH catalyst;

[0098] Literature 16 (Zhou, B.; Li, Y.; Zou, Y.; Chen, W.; Zhou, W.; Song, M.; Wu, Y.; Lu, Y.; Liu, J.; Wang, Y.; Wang, S., Platinum Modulates Redox Properties and 5-Hydroxymethylfurfural Adsorption Kinetics of Ni(OH)2 for BiomassUpgrading. Angewandte Chemie 2021, 60 (42), 22908-22914) Pt / Ni(OH)2 catalyst prepared;

[0099] P-HEOs catalyst prepared in reference 17 (Gu, K.; Wang, D.; Xie, C.; Wang, T.; Huang, G.; Liu, Y.; Zou, Y.; Tao, L.; Wang, S., Defect-Rich High-Entropy Oxide Nanosheets for Efficient 5-Hydroxymethylfurfural Electrooxidation. Angewandte Chemie 2021, 60 (37), 20253-20258);

[0100] Co3O4-NiO catalyst prepared in reference 18 (Jin, P.; Zhang, L.; Wu, Z.; Zhou, B.; Duan, Z.; Li, H.; Liu,H.; Deng, A.; Li, Q.; Zhang, Y.; Zhao, C.; Wang, S., Heterogeneous interfaceinduced Co3O4-NiO catalyst for efficient electrocatalytic 5-Hydroxymethylfurfural oxidation. Chemical Engineering Journal 2024, 481);

[0101] The CuO-SO4 catalyst prepared in reference 19 (Fan, Z.; Yang, Q.; Zhang, W.; Wen, H.; Yuan, H.; He, J.; Yang,HG; Chen, Z., Self-Reconstruction of Sulfate-Terminated Copper Oxide Nanorods for Efficient and Stable 5-Hydroxymethylfurfural Electrooxidation. Nano Lett. 2023).

[0102] Figure 8 The current density bar graphs of the catalysts prepared in Example 1 and References 1 to 19 in HMFOR at low voltages (1.2 V, 1.3 V and 1.4 V vs RHE) are shown in Table 1. Figure 8 It can be seen that the Cu provided by the present invention x O / CoO x@CF Heterogeneous catalysts have high current density in HMFOR at low voltage.

[0103] Fig. 9 CoO x @CF1 catalyst, Cu x O@CF catalyst and Cu x O / CoO x Electrochemical impedance spectroscopy (EIS) data of @CF heterogeneous catalysts and CoO x @CF1 catalyst, Cu x O@CF catalyst and Cu x O / CoO x Open circuit potential curves (OCP) of @CF heterogeneous catalysts in 1M KOH and 50mM HMF+1M KOH, where (a) is CoO x @CF1 catalyst, Cu x O@CF catalyst and Cu x O / CoO x EIS data of @CF heterogeneous catalysts, (b) CoO x @CF1 catalyst, Cu x O@CF catalyst and Cu x O / CoO x OCP curves of @CF heterogeneous catalyst in 1M KOH and 50mM HMF+1M KOH. Fig. 9 As shown in (a), with CoO x @CF1 catalyst and Cu x Compared with O@CF catalyst, Cu x O / CoO x The @CF heterogeneous catalyst showed a small semicircle in the electrochemical impedance spectroscopy test, indicating that the Cu x O / CoO x @CF heterogeneous catalysts have excellent conductivity and fast charge transport capabilities. The decrease in the open circuit potential of the electrochemical cell can reveal the changes in the adsorbate of the Helmholtz layer. The degree of decrease in the open circuit potential can roughly show the adsorption capacity of the catalyst for HMF. Therefore, for CoO x @CF1 catalyst, Cu x O@CF catalyst and Cu x O / CoO x The open circuit potential (OCP) and HMF adsorption behavior of the @CF heterogeneous catalyst were tested, and the results are shown in Fig. 9 As shown in (b). Fig. 9 As shown in (b), after adding 50 mM HMF, Cu x O / CoO xThe OCP of the @CF heterogeneous catalyst decreased the most (about 300 mV), followed by CoO x @CF1 catalyst and Cu x O@CF catalyst, the surface Cu provided by the present invention x O / CoO x The @CF heterogeneous catalyst has excellent conversion performance of HMF to FDCA.

[0104] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a copper-cobalt based heterostructure catalyst, characterized in that: The following steps are involved: The ethylene glycol solution of the soluble metal salt is drop-coated on the preheated metal foam substrate, and combustion occurs to form Cu on the metal foam substrate. x O / CoO y The film is obtained to obtain a copper-cobalt based heterogeneous structure catalyst; wherein 1<x<2, 1<y<4 / 3; the preheating temperature is ≥100°C; The soluble metal salt includes a soluble cobalt salt or a soluble copper salt; the concentration of the soluble metal salt in the ethylene glycol solution of the soluble metal salt is 0.1-1 mol / L; The metal foam substrate comprises a copper metal foam substrate or a cobalt metal foam substrate; The metal element in the soluble metal salt is different from the metal element in the metal foam substrate.

2. The preparation method according to claim 1, characterized in that: The drop coating amount of the ethylene glycol solution of the soluble metal salt is 100-400 μL / cm 2 .

3. The preparation method according to claim 1, characterized in that: The preheating temperature is 100-180°C.

4. The preparation method according to claim 1, characterized in that: The soluble cobalt salt includes cobalt nitrate; the soluble copper salt includes copper nitrate.

5. The copper-cobalt-based heterostructure catalyst prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The invention comprises a metal foam substrate and a Cu layer covering the surface of the metal foam substrate. x O / CoO y film.

6. Use of the copper-cobalt based heterostructure catalyst according to claim 5 in the electrocatalytic oxidation reaction of 5-hydroxymethylfurfural.

7. A method for electrocatalytic oxidation of 5-hydroxymethylfurfural, characterized in that: The following steps are involved: Electrolyze 5-hydroxymethylfurfural to produce an electrocatalytic oxidation reaction to obtain 2,5-furandicarboxylic acid; The working electrode used in the electrolysis is the copper-cobalt based heterostructure catalyst as described in claim 5.

8. The method according to claim 7, characterized in that The electrolysis temperature is 20-80°C and the time is 0.25-5.0h; The electrolyte used in the electrolysis includes a potassium hydroxide aqueous solution or a sodium hydroxide aqueous solution.

9. The method according to claim 7 or 8, characterized in that: The electrode system used in the electrolysis includes a three-electrode system, and the three-electrode system includes a working electrode, a reference electrode and a counter electrode; The reference electrode comprises a Hg / HgO electrode; The counter electrode includes a metal electrode or a graphite electrode.

Citation Information

Patent Citations

  • Copper oxide / cobalt oxide core-shell structural catalyst for electrolyzing water and preparation method thereof

    CN108671923A

  • Method for synthesizing organic acid ligand hybridized nickel-cobalt hydroxide catalyst through one-step hydrothermal method and application of organic acid ligand hybridized nickel-cobalt hydroxide catalyst

    CN116876032A